Radiocarbon dating : an archaeological perspective - Taylor, R. E. (Royal Ervin), 1938-; Bar-Yosef, Ofer (Left Coast Press, Inc., 2014)
"This volume is a major revision and expansion of Taylor's seminal book Radiocarbon Dating: An Archaeological Perspective. It covers the major advances and accomplishments of the 14C method in archaeology and analyzes factors that affect the accuracy and precision of 14C-based age estimates. In addition to reviewing the basic principles of the method, it examines 14C dating anomalies and means to resolve them, and considers the critical application of 14C data as a dating isotope with special emphasis on issues in Old and New World archaeology and late Quaternary paleoanthropology. This volume, again a benchmark for 14C dating, critically reflects on the method and data that underpins, in so many cases, the validity of the chronologies used to understand the prehistoric archaeological record."--Back cover